2023
DOI: 10.1186/s12911-023-02143-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient perspectives on the secondary use of their personal health information: an interview study

Abstract: Background The increased digitalisation of health records has resulted in increased opportunities for the secondary use of health information for advancing healthcare. Understanding how patients want their health information used is vital to ensure health services use it in an appropriate and patient-informed manner. The aim of this study was to explore patient perceptions of the use of their health information beyond their immediate care. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Proposals need to demonstrate that they understand the potential benefits, and perhaps more importantly, identify any potential risks for consumers in order to satisfy the consumer representation on the AIGG. Findings from the patient survey 20 , showed that there needed to be transparency and communication around what projects are using aggregated data. Therefore, ensuring that there is clear public communication will, in part, be the responsibility of the AIGG as well as the service intending to develop or implement the models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Proposals need to demonstrate that they understand the potential benefits, and perhaps more importantly, identify any potential risks for consumers in order to satisfy the consumer representation on the AIGG. Findings from the patient survey 20 , showed that there needed to be transparency and communication around what projects are using aggregated data. Therefore, ensuring that there is clear public communication will, in part, be the responsibility of the AIGG as well as the service intending to develop or implement the models.…”
Section: Resultsmentioning
confidence: 99%
“… A Buyer’s Guide to AI in Health and Care 19 A set of 10 questions required for making well-informed procurement decisions for AI systems. Topol The Topol Review – Preparing the healthcare workforce to deliver the digital future 20 An independent review conducted for the NHS on key digital technologies, barriers to its adoption and potential solutions to these barriers. Aotearoa NZ specific Hudson et al Te Ara Tika Guidelines for Māori Research Ethics 15 Provides a framework for researchers to work with Māori ensuring research is undertaken based on tikanga and matauranga Māori (Māori ethical principles and philosophies).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The individual and population metrics gathered can transform public health research, providing valuable insights into population health, disease trends, and effective interventions. Despite advancements in data availability, collection, and analysis ( 9 – 13 ), the use of PHI for research has been hindered by storage, cybersecurity, and data governance challenges ( 6 8 , 14 – 18 ). PHI has traditionally been stored in local databases or filesystems which lack sufficient cybersecurity and data governance.…”
Section: Introductionmentioning
confidence: 99%